Using critical theory: How to read and write about literature - Tyson, Lois 1950- (Abington, Oxon ; New York, USA: Routledge, 2021)
"Explaining both why theory is important and how to use it, Lois Tyson introduces beginning students of literature to this often daunting field in a friendly and readable style. The new edition of this textbook is clearly structured with chapters based on major theories frequently covered both in courses on literature and on critical theory. Key features include: coverage of major theories including reader-response theory, New Criticism (formalism), psychoanalysis, Marxism, feminism, lesbian/gay/queer theories, African American theory, and postcolonial theory practical demonstrations of how to use these theories to interpret short literary works selected from canonical authors including William Faulkner and Alice Walker a chapter on reader-response theory that shows students how to use their personal responses to literature while avoiding typical pitfalls sections on cultural criticism for each chapter that use our selected theories to interpret productions of popular culture . updated and expanded "basic concepts" sections updated and expanded "further study" sections for each chapter . updated and expanded theoretical vocabulary an expanded "next-step" appendix that suggests additional literary works for extra practice. Comprehensive, easy to use, and fully updated throughout, Using Critical Theory is the ideal first step for students beginning degrees in literature, composition, and cultural studies"--
Includes bibliographical references and index.
Keywords: Criticism; English Literature; Critical theory